SLE With Toxic Epidermal Necrolysis Like Presentation Successfully Treated with Plasmapheresis and Methyl Prednisolone Pulse: A Rare Case Report - Rajasekaran, Keerthana; Balaji Palanisamy, Nisanth; Manickam, Navakumar; Gopalan, Kannan; Ganga Vellaisamy, Seethalakshmi (Journal of Neonatal Surgery, 2025)
Toxic epidermal necrolysis (TEN), a life threatening dermatological condition, characterized by mucositis, epidermal detachment and erosions occurs mostly secondary to drugs with rare causes like systemic lupus erythematosus(SLE) have been implicated. TEN like presentation of SLE, a type of ACLE is being rarely reported due to the difficulty in differentiating it from drug induced TEN. Herein, we report a 25 year old male presenting with fever, weight loss, mucosal erosions, generalized fluid filled lesions and detachment of skin diagnosed as TEN like presentation of SLE. The patient showed positive anti Smith antibodies and was successfully treated with methyl prednisolone pulse therapy and plasmapheresis